Development of a plain-language library of educational resources for research participants. Issue 1 (6th July 2018) - Witte, Elizabeth; Winkler, Sabune J.; Myerson, Joanna; Kirby, Aaron; Biggers, Jessica; Do, Jacquelyn-My; Roth, Mary-Tara; Gateman, Alyssa K.; Cagliero, Enrico; Bierer, Barbara E.
Abstract : There is a paucity of educational resources for potential clinical trial participants, particularly resources in plain language, attentive to health literacy principles and translated into native languages. The New England Research Subject Advocacy Group was formed to explore common issues, interests, and concerns related to the experience of participation in clinical research and research participant safety. Specifically, the group sought to increase community awareness and trust through the development and distribution of publicly accessible informational resources. In support of these aims, the group developed a robust library of high-quality, plain-language educational materials covering topics in health research, research participation, and common research procedures, and translated the majority of the materials into an additional 15 languages. These resources have been downloaded over 130, 000 times. After English, the most common languages downloaded are Vietnamese, Spanish, and Korean.